Linking transport and translation of mRNAs with endosomes and mitochondria. (17th August 2021) - Müntjes, Kira; Devan, Senthil Kumar; Reichert, Andreas S; Feldbrügge, Michael
Abstract: In eukaryotic cells, proteins are targeted to their final subcellular locations with precise timing. A key underlying mechanism is the active transport of cognate mRNAs, which in many systems can be linked intimately to membrane trafficking. A prominent example is the long‐distance endosomal transport of mRNAs and their local translation. Here, we describe current highlights of fundamental mechanisms of the underlying transport process as well as of biological functions ranging from endosperm development in plants to fungal pathogenicity and neuronal processes. Translation of endosome‐associated mRNAs often occurs at the cytoplasmic surface of endosomes, a process that is needed for membrane‐assisted formation of heteromeric protein complexes and for accurate subcellular targeting of proteins. Importantly, endosome‐coupled translation of mRNAs encoding mitochondrial proteins, for example, seems to be particularly important for efficient organelle import and for regulating subcellular mitochondrial activity. In essence, these findings reveal a new mechanism of loading newly synthesised proteins onto endocytic membranes enabling intimate crosstalk between organelles. The novel link between endosomes and mitochondria adds an inspiring new level of complexity to trafficking and organelle biology. Abstract : This review highlights mRNA transport and translation on endosomes in different physiological contexts, and the role this process has in protein complex formation and subcellular protein targeting, including of mitochondrial proteins.